Polarización política en el Perú, 2000-2023 - Mejía Navarrete, Julio (2024)
This article analyzes the expansion of political polarization in Peru from 2000 to 2023. This political process has result in the division of society into opposing positions of us versus them, posing a significant threat to democracy by rendering consensus and agreements unlikely. The study highlights the political polarization in Latin America, before focusing in Peru by examining the social conditions, the central characteristics of political polarization, and its ideological, affective, and social aspects.